2020
DOI: 10.1371/journal.pmed.1003118
|View full text |Cite
|
Sign up to set email alerts
|

Health profile of adult special immigrant visa holders arriving from Iraq and Afghanistan to the United States, 2009–2017: A cross-sectional analysis

Abstract: Background Between 2,000 and 19,000 Special Immigrant Visa (SIV) holders (SIVH) from Iraq and Afghanistan resettle in the United States annually. Despite the increase in SIV admissions to the US over recent years, little is known about the health conditions in SIV populations. We assessed the burden of select communicable and noncommunicable diseases (NCDs) in SIV adults to guide recommendations to clinicians in the US. Methods and findings We analyzed overseas medical exam data in Centers for Disease Control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In this study, the reasons for the high incidence of chronic diseases among Chinese immigrants include the following. First, the average age of the participants in this study was older than that in the other two studies [ 16 , 24 ]. The average age in this study was 52.21 years; however, only 7.4% of the participants were aged 45–64 years in the study of Kumar, and the average age was 42.02 years in the study of Lo.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In this study, the reasons for the high incidence of chronic diseases among Chinese immigrants include the following. First, the average age of the participants in this study was older than that in the other two studies [ 16 , 24 ]. The average age in this study was 52.21 years; however, only 7.4% of the participants were aged 45–64 years in the study of Kumar, and the average age was 42.02 years in the study of Lo.…”
Section: Discussionmentioning
confidence: 78%
“…A 17-year National Health Interview Survey (1999–2015) identified that the prevalence of chronic diseases among Mexican, Puerto Rican, Cuban, Dominican, and Central/South American immigrants was 23.1%, 40.0%, 38.5%, 28.0% and 23.5%, respectively [ 16 ]. A cross-sectional health condition analysis of immigrants from Iraq and Afghanistan to the United States between 2009 and 2017 showed that 56.5% of these immigrants were overweight or obese, 2.4% reported hypertension and 1.1% reported diabetes [ 24 ]. In this study, the reasons for the high incidence of chronic diseases among Chinese immigrants include the following.…”
Section: Discussionmentioning
confidence: 99%
“…was also found that 35.3% of them were obese as a sign of an unhealthy diet (BMI over 24.9%). Similarly, it was reported that 38% of Iraqi immigrant women were overweight, and hypertension was an important problem with obesity [21]. As an indicator of nutritional deficiency, the prevalence of anemia in Syrian migrant women was 45% [22].…”
Section: Discussionmentioning
confidence: 96%
“…Afghan refugee women have been resettling in the United States since the 1980s as a result of displacement due to protracted wars and conflicts in Afghanistan. Afghan women are now aging and face multiple layers of inequities and challenges to maintaining their health and well-being (Kumar et al, 2020; Siddiq et al, 2020). Particularly, Afghan women may face increased burden of chronic disease and mental health issues and face challenges in accessing preventive health services (Naja et al, 2019; Yun et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Like other U.S. immigrant and refugee groups, Afghan women are at risk for worsening health outcomes the longer they reside in their country of resettlement. Although prevalence data on chronic diseases among Afghans are limited, emerging research on refugees suggests this population faces increasing rates of chronic diseases the longer they reside in the United States (Kumar et al, 2020; Yun et al, 2012). This may be due to the increased risk of developing chronic health issues in later life, multi-morbidity, sedentary lifestyle, and decreased quality of life (Debesay et al, 2022).…”
Section: Introductionmentioning
confidence: 99%